Effects on Selected Soil Properties of Subsurface Banding and Surface Broadcasting Pelletized Poultry Litter on Cotton. Issue 3 (May 2018) - Adeli, Ardeshir; Brooks, John P.; Read, John J.; Feng, Gary; McCarty, Jack C.; Jenkins, Johnie N.
Abstract : ABSTRACT: The response of soil chemical, physical, and biological properties to subsurface band and surface broadcast applications of pelletized poultry litter (PPL) to row crops has not been well documented in Mississippi agroecosystems. This study was conducted in a no-till system on Caledonia silt loam and in a conventional tillage system on Marietta loam, to determine the effects of PPL placement relative to inorganic N fertilizer on selected soil health indicators, including total C, penetration resistance, and microbial activity. The experimental design at each site was a randomized complete block with three treatments replicated four times. Treatments were PPL at the rate of 6.7 Mg ha −1, state-recommended inorganic N fertilizer, and an unfertilized control. Inorganic N fertilizer was applied as urea-ammonium nitrate (32% N). Relative to inorganic N fertilizer, applying PPL in subsurface band for 4 years (2010–2103) increased soil P by 48% and total C by 17%. Regardless of the PPL application method, soil penetration resistance was 19% lower with PPL than fertilizer N. Residual NO3 -N levels in the soil layers did not differ between PPL and unfertilized control; however, levels were greatest with inorganic N fertilizer. Additionally, applying PPL in subsurface bands increased soil dehydrogenase activity and cephalothin-resistant heterotrophic plate count bacteria as compared with the control and inorganic N fertilizer. Cotton lint yield was significantly greater with PPL than with inorganic N fertilizer in 2012 in Caledonia silt loam soil (1, 244 vs. 1, 128 kg ha −1 ) and in 2013 in Marietta loam soil (1, 369 vs. 1, 078 kg ha −1 ). Subsurface band placement of PPL appeared to be very useful in improving soil chemical, physical, and biological properties.